Application Calibration Based on Energy Consumption Model in Optimal Design of Green Buildings. (6th September 2021) - Xue, Feiran; Zhao, Jingyuan
Abstract : Buildings will generate considerable resource and energy consumption, environmental impact, and costs throughout their entire life cycle. Life cycle assessment and life cycle cost methods have become widely used building sustainability evaluation methods internationally due to their long-term comprehensive evaluation perspectives and scientific quantitative calculation methods. In response to energy consumption management issues in green buildings, a questionnaire survey was conducted to investigate the concepts of sustainable development, green environmental protection, and energy consumption management of construction enterprise personnel. Through the survey, it can be seen that corporate executives generally have a sense of sustainable development and pay more attention to sustainable competition and the green development of enterprises. Approximately 90% of executives understand energy consumption models. Only 10% of employees do not understand, but they are acquired by the company's frontline employees. The result of the feedback is just the opposite. Frontline workers pay little attention to the long-term development of the company. Only about 5% of employees are proficient in the energy management system, but the proportion of completely unknown is as high as 20%, indicating that the overall energy management awareness of Chinese enterprises still needs to be strengthened. Secondly, through design experiments, the energy-saving management effect of the energy consumption model was observed and analyzed. From the power saving and load test, we found that the monitoring of the energy consumption model is helpful for companies to choose more energy-efficient building circuit designs, achieving an average annual energy-saving effect of about 8%, so as to achieve the purpose of energy saving.